Custom-Made Foot Insoles on Dynamic Balance in Children with Flexible Flat Feet: A Community-Based Study - Nur Rachmat; Bambang Kuncoro; Dody Suprayogi; Atika Febri Anggraini; Annisa Dwi Nur Kusumawardani; Indra Yulianti (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Flexible flat feet in children are common in community and school-aged populations and may be associated with altered lower-limb biomechanics, impaired postural control, and reduced dynamic balance, potentially affecting mobility, participation, and safety in daily activities. Although custom-made foot insoles are widely prescribed, evidence regarding their functional effects on dynamic balance in community-based pediatric settings remains limited. This study aimed to evaluate the effects of custom-made foot insoles on dynamic balance among children with flexible flat feet in a community-based rehabilitation context. A pre–post intervention study was conducted involving 40 children (mean age 10.05 ± 1.04 years). Dynamic balance was assessed using the Balance Beam Test before and after the intervention. Changes in balance performance were analyzed using the Wilcoxon signed-rank test, with effect size calculated using Cohen’s d. Dynamic balance scores improved significantly after insole use (Z = −3.995, p < 0.001), with a large effect size (d = 0.81). Greater improvements were observed in children with lower baseline balance. These findings support the potential role of custom-made foot insoles within community-based rehabilitation strategies to enhance functional balance and promote safe participation among children.